(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article describes in detail about the development of aesthetic culture of students in painting classes, the importance of education in the development of aesthetic culture of students, the essence and tasks of the educational process aimed at any goal that develops aesthetic culture of students in painting classes.